Magnitude and associated factors of Pityriasis Versicolor among patients attending Dermatovenereology Outpatient Department at the University of Gondar Comprehensive Specialized Hospital, Northwest Ethiopia - Tilaye, Mengistu; Sinknew, Abebe; Mekuriaw, Alemneh; Tsehay, Asmamaw Ketemaw (Journal of Current Health Sciences, 2023)
Pityriasis versicolor (PV) is a chronic superficial fungal infection caused by Malassezia species. It is the most common dermatologic disorder in tropical countries including Ethiopia and skin discoloration is the principal morbidity resulting from pityriasis versicolor. Therefore, this study assess the prevalence and associated factors of PV among patients attending Dermatovenereology clinic at the University of Gondar Comprehensive Specialized Hospital. Hospital based cross sectional study design was employed. Systematic random sampling was used and a total of 406 participants who attended Dermatovenereology OPD were included in the study. Data were collected by interview and physical examination. Then it was checked, coded, entered into Epi-Info version 7 and analyzed using Stata version 14. Both bivariable and multivariable logistic regression were employed to identify factors associated with PV. Adjusted odds ratio with their corresponding 95% CI and P-value were calculated. A P-value less than 0.05 was used to declare statistically significant variables. The overall magnitude of PV among patients attending Dermatovenereology OPD at the UGCSH was 12.6% (95%CI; 9.2%, 15.0%).Those who had a diploma and above education  [AOR: 95% CI; 4.67 (1.18, 18.47)], excessive sweating [AOR: 95% CI; 4.75 ( 1.92, 8.76)] being male [AOR: 95%CI; 4.19 (1.92, 9.14)], practicing regular exercise [AOR: 95% CI;  4.11 (1.93, 8.76)] and wearing heavy clothes [AOR: 95% CI; 2.53 (1.24, 5.15)] were found to be statistically significantly associated with PV. This study found that the magnitude of Pityriasis versicolor was relatively lower. The study revealed that educational status (diploma and above), male gender, habit of regular exercise, excessive sweating and wearing heavy cloths were significantly associated with Pityriasis Versicolor. It is recommended that high risk patients receive close follow up and health professionals should provide health education sessions in waiting rooms about the identified risk factors.